Responsibilities of the Land Deed Making Office in the Preparation of a Sale Purchase Deed on a Guarantee Without the Consent of the Object Owner - Bildia, Zahra; Handayani, Sri Wahyu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The responsibility of Land Deed Officials (PPAT) in ensuring the validity of land sale and purchase transactions in Indonesia, as well as the legal consequences in the event of negligence. As a state based on the rule of law based on Pancasila and the 1945 Constitution, Indonesia requires authentic evidence to ensure legal certainty, order, and justice. Authentic deeds, drawn up by public officials such as notaries and PPATs, play a crucial role in every legal act, including land transactions. Judicial Review Decision Number 47 PK/Pdt/2025, in which the PPAT allegedly abused his authority and made a deed that did not comply with procedures, resulted in losses for one of the parties. The research method used was normative juridical, with a conceptual and legislative approach, as well as a literature study to analyze secondary data such as books, journals, and regulations. The results of the study indicate that PPATs have a responsibility to ensure the legality of transactions and prevent future disputes. Negligence in the administrative process, such as not promptly transferring the title to a certificate, can create legal uncertainty. The legal consequences of unlawful acts by PPATs can render the deed they have drawn up null and void and trigger disputes. This study concludes that legal protection for buyers in good faith is crucial. Therefore, improvements to the land administration system and closer collaboration between Land Deed Officials (PPAT) and the National Land Agency (BPN) are needed to create legal certainty and protect community rights.